2015
DOI: 10.7314/apjcp.2015.16.4.1559
|View full text |Cite
|
Sign up to set email alerts
|

Male Breast Cancer: a 24 Year Experience of a Tertiary Care Hospital in Pakistan

Abstract: States has shown a significant increase in the incidence of MBC whereas a steady low rate has been observed in European studies. (Kaushik et al., 2014) There is still a paucity of randomized controlled trials and treatment for MBC is based on treatment for FBC.The general variation of MBC across the globe is similar to FBC with higher rates in North America and Europe and lower rates in Asia. (Chikaraddi et al., 2012;Kaushik et al., 2014) Materials and MethodsThis retrospective review was carried out at The A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…2019-0391-2980). This study included 19 cases of MBC reported by Jamy et al from the same study institution in 2009 [ 11 ]. Data on demographics, clinicopathological features, and treatment modalities of all MBC patients were retrieved from the institution’s breast cancer database.…”
Section: Methodsmentioning
confidence: 99%
“…2019-0391-2980). This study included 19 cases of MBC reported by Jamy et al from the same study institution in 2009 [ 11 ]. Data on demographics, clinicopathological features, and treatment modalities of all MBC patients were retrieved from the institution’s breast cancer database.…”
Section: Methodsmentioning
confidence: 99%
“…[4] However, literature has shown that exposure to estrogen can cause terminal lobules to develop carcinoma in the male breast. [28] In our study series, infiltrating ductal carcinoma-NOS type was the only malignant type. The same histological type was also found to common by others such as Fentiman et al, [9] in 2006, and Chikaraddi et al, [2] in 2012.…”
Section: Discussionmentioning
confidence: 98%
“…Breast carcinoma in men is rare which most often occurs at or after the age of 60 years. The cause of MBC (male breast carcinoma) remains unclear, however several risk factors were identified such as age of patient, genetic predisposition, anatomic factors and hormone metabolism abnormalities related to elevated estrogen or prolactin levels [1].…”
mentioning
confidence: 99%